Implementation of a Pharmacy Clinical Instructor Model to Facilitate Experiential Learning within Saskatchewan’s Entry-to-Practice Doctor of Pharmacy Program - Steven Kary; Cheryl A. Camillo; Shauna Gerwing; Zack Dumont (Health Reform Observer - Observatoire des Réformes de Santé, 2023)
In response to nationally endorsed changes in pharmacy curricula, the University of Saskatchewan College of Pharmacy and Nutrition (CoPN) sought to expand experiential learning for its pharmacy program. In 2010, Canada’s faculties and deans of pharmacy committed to implementing entry-to-practice Doctor of Pharmacy (PharmD) programs in all schools by 2020. The expansion and change in credentialing of Canada’s pharmacy training from baccalaureate programs was intended to ensure graduates possess the competencies required within the modern scope of pharmacy practice. To further this transition, the Canadian Council for Accreditation of Pharmacy Programs increased the required hours of students’ experiential learning. In Saskatchewan, pre-existing operational and financial pressures on the CoPN, coinciding with the provincial health system’s amalgamation from twelve regional health authorities to a single health authority, prompted a collaborative approach. To address the growing need for practical experience within the Saskatchewan Health Authority, the CoPN implemented clinical instructor positions within tertiary care centres in Saskatoon and Regina. This unique approach among PharmD programs provided financial stability and accountability to student learning, although early student feedback identified several challenges with this model. These findings about the clinical instructor model can guide the ongoing implementation of experiential learning within PharmD and other health care professional programs.